2017
DOI: 10.1139/cjce-2017-0300
|View full text |Cite
|
Sign up to set email alerts
|

Development of artificial neural network and multiple linear regression models in the prediction process of the hot mix asphalt properties

Abstract: The oscillation of asphalt mix composition on a daily basis significantly affects the achieved properties of the asphalt during production, thus resulting in conducting expensive laboratory tests to determine existing properties and predicting the future results. To decrease the amount of such tests, a development of artificial neural network and multiple linear regression models in the prediction process of predetermined dependent variables air void and soluble binder content is presented. The input data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Although the mechanistic constitutive methods allow a rational and in-depth analysis of the material response to be performed [10][11][12][13][14][15][16][17], statistical or machine learning approaches are gaining considerable success in the academic community due to the good reliability of their predictions [18][19][20][21], even if they are not physically based. Nevertheless, it has also been reported that statistical regressions of experimental data can produce less accurate predictions than machine learning methods, specifically with regard to Artificial Neural Networks (ANNs) [22][23][24][25][26][27]. Recently, Lam et al [28] have found that a multiple regression analysis (coefficient of determination, R 2 , equal to 0.790) is less reliable than an ANN approach (R 2 = 0.925) searching the analytical model to infer compressive strength of roller-compacted concrete pavement from steel slags aggregate and fly ash levels replacing cement.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanistic constitutive methods allow a rational and in-depth analysis of the material response to be performed [10][11][12][13][14][15][16][17], statistical or machine learning approaches are gaining considerable success in the academic community due to the good reliability of their predictions [18][19][20][21], even if they are not physically based. Nevertheless, it has also been reported that statistical regressions of experimental data can produce less accurate predictions than machine learning methods, specifically with regard to Artificial Neural Networks (ANNs) [22][23][24][25][26][27]. Recently, Lam et al [28] have found that a multiple regression analysis (coefficient of determination, R 2 , equal to 0.790) is less reliable than an ANN approach (R 2 = 0.925) searching the analytical model to infer compressive strength of roller-compacted concrete pavement from steel slags aggregate and fly ash levels replacing cement.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the k-nearest neighbor model—an effective machine learning algorithm—was applied to predict the moisture susceptibility of HMA [ 14 ], which suggested that this machine learning model should be used for accurate prediction of the vital properties of the HMA. Androjić et al [ 15 ] studied and compared two popular machine learning models namely ANN and multiple linear regression (MLR) for prediction of different HMA properties (air void and soluble binder content), and concluded that both applied machine learning models are suitable for prediction of the HMA properties. However, ANN is better than MLR at predicting the air void content, whereas MLR is better than ANN in predicting soluble binder content.…”
Section: Introductionmentioning
confidence: 99%
“…Researches such as Loia et al (2000), Quintero et al (2005), Šelih et al (2008), and Jajac et al (2009) can be highlighted as the one where ANNs were used for solving problems on both tactical and strategic management levels based upon Turban's DSS concept. Such approach bloomed in 2010s when more and more researchers very efficiently applied ANNs for solving structured problems that occur on operational level (Gesoglu et al, 2010;Xiao et al, 2010;Ozgan, 2011;Ciresan et al, 2012;Singh et al, 2013;Ozturk and Kutay, 2014;Zavratnik et al, 2016;Androji and Marovi , 2017;Zhang et al, 2018;Gong et al, 2019) as well as for solving semi-structured and unstructured problems that occur on tactical and strategic levels as a part of various DSS'es (Durduran, 2010;Coutinho-Rodrigues et al, 2011;Dahal et al, 2013;Du et al, 2014;Jajac et al, 2014;Jajac et al, 2015;Han et al, 2016;Marovi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%